2012
DOI: 10.1007/s11748-011-0827-8
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term results of the box pulmonary vein isolation and the cryo-maze procedure for chronic atrial fibrillation associated with mitral valve disease

Abstract: The cryo-maze procedure was rather effective for eliminating chronic AF associated with both mitral and tricuspid valve disease, but there were a few cases with new atrial tachycardia. The box pulmonary vein isolation was useful in solitary mitral valve cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 18 publications
0
22
0
1
Order By: Relevance
“…In 10 studies (35.7%) mitral surgery was the main procedure performed in association with AF ablation, while in the remaining studies various types of main procedures (coronary surgery, valve surgery, aortic surgery, etc) were performed aside of AF ablation. Four studies enrolled only patients rheumatic valve disease (RVD) in both study groups, while 4 more studies reported a variable quota of RVD ranging between 50% and 70% of the population, while in the remaining 20 studies the incidence of RVD was not clearly stated.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In 10 studies (35.7%) mitral surgery was the main procedure performed in association with AF ablation, while in the remaining studies various types of main procedures (coronary surgery, valve surgery, aortic surgery, etc) were performed aside of AF ablation. Four studies enrolled only patients rheumatic valve disease (RVD) in both study groups, while 4 more studies reported a variable quota of RVD ranging between 50% and 70% of the population, while in the remaining 20 studies the incidence of RVD was not clearly stated.…”
Section: Resultsmentioning
confidence: 99%
“…23,35,36 Ten (35.7%) were prospective observational studies, of which two had propensity adjustment. 3,4,21,22,24,25,27,31,32,37 The remaining 15 studies (53.6%) were retrospective observational, of which 3 were propensity adjusted. 5,19,20,26,[28][29][30]33,34,38,39,[44][45][46][47] In 16 studies (57.1%) all the patients enrolled presented exclusively non-paroxysmal AF forms and these studies constituted the "non-paroxysmal AF subgroup."…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study reports a mean FU of 9.1 years (7.7 years to 10.5 years) for 164 patients after catheter ablation at our institution which represents 1,492 PY of FU. There is currently limited long‐term FU data after catheter ablation of AF . Our study includes, to the best of our knowledge, the maximum number of patients followed‐up at a single center beyond 5 years after ablation with outcomes for 178 patients (164 who completed the study requirements and 14 who died during the FU).…”
Section: Discussionmentioning
confidence: 99%